2017
DOI: 10.1186/s12877-017-0482-8
|View full text |Cite
|
Sign up to set email alerts
|

Advance directives and power of attorney for health care in the oldest-old – results of the AgeQualiDe study

Abstract: BackgroundCompletion of advance directives (ADs) and power of attorney (POA) documents may protect a person’s autonomy in future health care situations when the individual lacks decisional capacity. As such situations become naturally much more common in old age, we specifically aimed at providing information on (i) the frequency of ADs/POA in oldest-old individuals and (ii) factors associated with having completed ADs/POA.MethodsWe analyzed data of oldest-old primary care patients (85+ years; including commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
2
15
0
2
Order By: Relevance
“…This trust was well documented in prior studies, e.g. the AgeQualiDe study showed that 28.3% of oldest old patients (≥85 years) were not interested in written documents as they believed that their GP and family members would make the right decisions for them [ 12 ]. In contrast to these long-standing relationships, external ACP facilitators would need to start from scratch and require considerably more time.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This trust was well documented in prior studies, e.g. the AgeQualiDe study showed that 28.3% of oldest old patients (≥85 years) were not interested in written documents as they believed that their GP and family members would make the right decisions for them [ 12 ]. In contrast to these long-standing relationships, external ACP facilitators would need to start from scratch and require considerably more time.…”
Section: Discussionmentioning
confidence: 60%
“…Despite these developments, the prevalence of ADs is low; in Belgium and the Netherlands, for example, 2–3% of persons aged below 60, about 10% of those aged ≥60, and up to 23% of relatives of decedents have ADs [ 10 , 11 ]. In Germany, the prevalence of ADs in the general population was between 2.5 and 10%, while a survey of GP patients ≥85 years reported that 69% have an AD and 64.6% a PA [ 12 , 13 ]. Beside notaries, general practitioners (GPs) are the preferred contact persons for discussing end-of-life issues and preparing such documents [ 14 , 15 ], yet little research has been conducted in primary care settings [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having an AD and advance care plan improve the quality of end-of-life care and increase the satisfaction of elderly patients and their families ( 10 ). Several studies have reported that over 50% of aged nursing home residents have an AD in the United States ( 11 , 12 ) and in Germany ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…; n = 726/21.8%). For further details of the Age-CoDe and AgeQualiDe study sampling, see Luck et al (2007Luck et al ( , 2017. All patients who participated in the studies provided written informed consent prior to their participation.…”
Section: Samplingmentioning
confidence: 99%